Developing Buildings Permits Systems Platforms (BPSP) for driving change to introduce GeoBIM potentials, challenges, and opportunities - Obaid Talal Aljobaly; Mohammed Maatouk; Emad Qurnfulah (Journal of Applied Geospatial Information, 2022)
Cities growth requires development in tools and applications to manage achieving city strategic vision with clear smart policies, which is challenging to achieve with traditional methods. So, the importance of adopting integrated technologies like BIM, GIS, and GeoBIM is becoming essential and beneficial. Many countries have developed using such technologies to enhance the performance of Building Permits Systems (BPS). The need to build a system that unifies practices, standards, and protocols within one place in a manageable platform shall enhance the performance of BPS. So, the aim is to assess the capabilities of implementing GeoBIM in Saudi BPSP municipalities for developing procedures and workflows and to define the potentials and barriers of change in systems. So, the research focused on developing existing systems with a semi-structured interview evaluates the capabilities and workflows for adopting GeoBIM in the Riyadh, Jeddah, and Mecca municipalities. In conclusion, the research results 21 factors of GeoBIM implementation that shall initiate a foundation for further studies fulfilling gaps in such study areas.